The second revolution of relativity - Merouani, Amar (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Energy, this vital entity that we need, and that everyone consumes and liberates, in different forms, has been since the dawn of time the greatest concern of the human being. Over the centuries, energy has transformed lifestyles in all societies of the world, contributing to the emergence of new cities and major cosmopolitan cities. Scientific research has contributed to much of this extraordinary advance of energy in the conquest of the world, thanks to the many works and discoveries of scientists from the golden age of Islamic civilization to the renaissance in Europe, to the great technological revolution that has emerged in the North and in the South. The continuous need for energy has always been the main driver, for various discoveries, whether related to energy matter or those related to energy reactions. Between pure matter and an active reaction, energy has become the focus of several hybrid studies, manipulating energy as a source on the one hand, and as a finished product on the other. While most of the work carried out on the electric current, during the first years of the 17th century [1], showed the precariousness of the materials as regards their conductivity, the arrival on the scientific scene of new chemical elements, discovered then around the 18th century, have strengthened the quality of the works and consequently the improvement of the electrical productivity in the world. Nuclear energy will suffer the same fate of development as that of electrical energy, passing through critical periods, especially those relating to the discovery of high-activity materials [2]. Nevertheless, the arrival at the beginning of the 18th of the famous formula of Albert Einstein on relativity, (E= mc2) [3], put an end to the major concerns of scientists on energy, to know finally, the nature and value of the energy compensation of the material during its activity. We, in turn, consider that Albert Einstein’s formula is not entirely sufficient to decipher the true energetic reality of matter. Our work is a re-shaping of the relativistic formula, not only from the physical point of view but also from the mathematical point of view. As a result, our contribution to this restoration pleads for a new apprehension of the atom as an «original copy of the universe» which has an infinity of nanoscopic particles, which remain active within matter, Chemically active and physically metastable. This extrapolation of the relativistic formula will recognize to energy the other side of its independence from matter.